Car Accident Due to Horse Crossing the Motorway: Two Case Reports - Kılıç, Serbülent; Cantürk, Gürol (The Bulletin of Legal Medicine, 2018)
Basic Commercial Court in Ankara wanted a report from our department of forensic medicine about two injury cases due to animal vehicle collision. The reports should include the disability rate and the duration of unfunctionality. After the examination we prepared the reports. Both vehicle collisions happened due to free ranging horse crossing the motorway. Both cases had different types of injury due to trauma. Vehicle collision due to horse crossing the motorway is rarely met in Turkey.Our first case is a man that had upper extremity and facial injury. He uses prothesis due to ear amputation. He has a scar tissue on the right side of his face and left forearm. The other case is three-years-old boy that had cranial bone fracture and cranial hematoma. He has also hemiparesis of the right side of body. Both cases have neurologic sequels but they have no psychiatric sequels. In literature, animal vehicle collisions involve lots of animal species such as kangaroo, deer, camel and moose. Animal vehicle collision involving the horses is rarely met. Forensic medicine specialists should state the causal link between traumatic events and disabilities in order to help justice. Our aim to present the current two cases is investigation of injuries of animal related collision and makes forensic medicine specialists pay attention to the subject of preparing reports about such cases.Key words: Animal vehicle collision; death; disability; horse; injury; motorway.
Keywords: animal vehicle collision; death; disability; horse; injury; motorway